1998
DOI: 10.1095/biolreprod58.2.439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress on the Reproductive Performance of Rainbow Trout (Oncorhynchus mykiss)1

Abstract: We investigated the effects of stress over the final stages of sexual maturation on the reproductive performance of female rainbow trout, Oncorhynchus mykiss. Stress was administered over the period of early vitellogenesis (1.5 mo), late vitellogenesis-final maturation (1.5 mo), or during both periods (3 mo). Each stress treatment and control was triplicated, with eight females in each replicate (n = 24 fish per treatment). The eggs and progeny of each female were kept separate, and observations were made for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 45 publications
6
88
1
Order By: Relevance
“…Contreras-Sánchez et al (1998) found similar results in Oncorhynchus mykiss submitted to moderate stress during vitellogenesis. The results obtained in this study can be attributed to other factors such as: stress due to confinement, affecting the quality and size of oocytes during maturation (Foo and Lam, 1993;Campbell et al (1994); Sumpter et al (1994); Pankhurts and Van der Kraak, 1997), and/or the environmental quality of contention ponds (Schreck, 1981;Wendelaar-Bonga, 1997) and/or the nutritional conditions of females (Watanabe, 1990;Izquierdo et al, 2001), specially the accumulation of lipides in vitellogenesis (Wiegand, 1996).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Contreras-Sánchez et al (1998) found similar results in Oncorhynchus mykiss submitted to moderate stress during vitellogenesis. The results obtained in this study can be attributed to other factors such as: stress due to confinement, affecting the quality and size of oocytes during maturation (Foo and Lam, 1993;Campbell et al (1994); Sumpter et al (1994); Pankhurts and Van der Kraak, 1997), and/or the environmental quality of contention ponds (Schreck, 1981;Wendelaar-Bonga, 1997) and/or the nutritional conditions of females (Watanabe, 1990;Izquierdo et al, 2001), specially the accumulation of lipides in vitellogenesis (Wiegand, 1996).…”
Section: Discussionsupporting
confidence: 74%
“…The embryonic and larval survival had values that were not significantly different among groups and were similar to those found by Contreras-Sánchez et al (1998). However, it is possible that physiological responses to stress might have affected ontogenesis and larval development in a different way, as much as the nutritional conditions of females (Lam, 1985;Foo and Lam, 1993;Campbell et al, 1994), and/or the incubation of eggs and manipulation of larvae, also affecting reproductive products (Laine and Rajasilta, 1999;Schreck, 2000).…”
Section: Discussionmentioning
confidence: 72%
“…However, in light of the reported increases in oocyte cortisol content following on from increases in maternal plasma cortisol concentrations (Stratholt et al 1997, Contreras-Sánchez et al 1998, Eriksen et al 2006, Leatherland et al 2010, it would appear that the maternal blood-oocyte barrier is only partially effective. Furthermore, as increases in oocyte cortisol levels before their fertilization affect the At all developmental stages, cortisol is predominantly present as an unconjugated steroid, with traces (4-6% of the total counts) as a sulphated steroid, whereas cortisone is largely present in the form of a sulphate.…”
Section: Embryo Tissuesmentioning
confidence: 99%
“…The physiological significance of this finding is not clear; however, exposure to stress and the ability to cope with stress are likely to be important factors in the number and quality of the gametes produced. Studies in the rainbow trout revealed that exposure to stress during oogenesis resulted in lower quality of the gametes produced (4,7). Further studies are required to fully establish the implications of exposure to stress on reproductive success.…”
Section: Anchoring Individual Transcriptomes With Reproductive Phenotypementioning
confidence: 99%